Photodegradation of Liquid Waste Using ZnO/Graphene-Like Composites - Desi Heltina; Raihan Daffansyah Sinaga; Yayan Setiawan; M Iwan Fermi; Amun Amri (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2024)
Abstract: The development of industries such as textiles, dyes, plastics, medicines, cosmetics, and others is increasing along with a rise in production, leading to a high amount of liquid waste generated. Non-biodegradable, toxic, and carcinogenic liquid waste can cause environmental pollution to surrounding water. To address this challenge, biomass waste such as palm kernel shells can be used to treat liquid waste by compositing it with photocatalyst materials. Therefore, this research aimed to obtain ZnO/graphene-like composites to degrade liquid waste. ZnO/Graphene-like composites were synthesized using the solvothermal method, followed by calcination. The performance test was carried out by varying the types of methylene blue, methyl orange, and phenol waste with an initial concentration of 10 ppm, alongside the variations of ultraviolet (UV) and mercury lamps. Subsequently, characterization was carried out using SEM, XRD, FTIR, BET, UV-Vis DRS, and UV-Vis Spectrophotometer. The results showed that the percent degradation of methylene blue under UV and mercury were 83.42% and 84.93 % respectively, while methyl orange in the same conditions was 94.83% and 97.17%, respectively. Furthermore, the percent degradation of phenol in UV light and mercury were 86.03% and 89.62%, respectively. This showed that the use of mercury lamps on methyl orange was more effective than UV lamps on methylene blue and phenol.Abstrak: Perkembangan industri seperti industri tekstil, pewarna, plastik, obat-obatan, kosmetik, dan lain-lain semakin meningkat dengan seiring bertambahnya jumlah produksi sehingga jumlah limbah yang dihasilkan juga meningkat salah satunya limbah cair. Limbah cair yang tidak dapat terurai secara biologis, beracun, dan karsinogenik ke perairan terdekat mengakibatkan pencemaran lingkungan. Disisi lain, limbah biomassa seperti cangkang sawit dapat dimanfaatkan untuk mengolah limbah cair, salah satunya mengkompositkan dengan material fotokatalis. Penelitian ini bertujuan memperoleh komposit ZnO/graphene-like untuk mendegradasi limbah cair. Komposit ZnO/Graphene-like disintesis dengan metode solvothermal dan dikalsinasi. Uji kinerja komposit ZnO/graphene-like dilakukan dengan menvariasikan jenis limbah methylene blue, methyl orange dan fenol dengan konsentrasi awal masin-masing 10 ppm serta dengan variasi lampu UV dan lampu merkuri. Komposit ZnO/Graphene-like dikarakterisasi menggunakan SEM, XRD, FTIR, BET, UV-Vis DRS dan UV-Vis Spektrofotometer. Hasil penelitian menunjukkan bahwa persen degradasi methylene blue di bawah sinar UV dan merkuri masing-masing sebesar 83,42% dan 84,93%, sedangkan methyl orange dengan sinar UV dan merkuri masing-masing sebesar 94,83% dan 97,17%. Selanjutnya, persen degradasi fenol dengan sinar UV dan merkuri masing-masing adalah 86,03% dan 89,62%. Hal ini menunjukkan bahwa penggunaan lampu merkuri pada methyl orange lebih efektif dibandingkan lampu UV pada methylene blue dan fenol.